EMPOWERMENT OF COCOA FARMERS (THEOBROMA CACAO L.) DURING PRE AND POST-HARVEST IN EFFORT OF QUALITY IMPROVEMENT OF COCOA COMMODITY IN KOLAKA - Yolanda Fitria Syahri; H. Hastuti (Universitas Sembilanbelas November Kolaka, 2017)
Kolaka is known as